A new genus and new species of palaemonid shrimp (Decapoda: Caridea), associated with the deep-sea crinoid Metacrinus rotundus (Echinodermata: Isocrinidae), from Suruga Bay, Japan - Komai, Tomoyuki; Sakiyama, Hiroki (Zootaxa, 2023)
Metacrimenes fenestra, a new palaemonid genus and species is described on the basis of an ovigerous female and one juvenile specimen from Suruga Bay, central Japan. The specimens were associated with the stalked crinoid Metacrinus rotundus Carpenter, 1885, collected at a depth of 131–200 m. Photographs taken in situ indicate that the shrimp lives ectosymbiotically on its crinoid host. The greatly reduced bud-like exopod on the third maxilliped links the new genus to Mesopontonia Bruce, 1967 (Indo-West Pacific) and Waldola Holthuis, 1951 (East Pacific), in which the exopod is absent, but the presence of antennal spine on the carapace and the non-elongate, symmetrical second pereopods immediately distinguish Metacrimenes n. gen. from these genera. Molecular phylogenetic analysis using a dataset concatenating two mitochondrial markers (16S rRNA and COI genes) clusters the new genus with Paraclimenes gorgonicola (Bruce, 1967), two species of Mesopontonia and Brucecaris tenuis (Bruce, 1969). However, in Paraclimenes Bruce, 1995 and Brucecaris Marin & Chan, 2006, the third maxilliped exopod is normally developed, flagellum-like. Other differentiating characters between the new taxon and the presumably allied taxa are discussed.